The influence of applicant's and rater’s sex on decision making in hiring simulation - Norvaišaitė, Justė; Mikuličiūtė, Vita (Psichologija, 2021)
Gender stereotypes have determined that the concepts of management and leadership are more associated with men than women. There are more men working in management positions than women in various countries, including Lithuania. The most widely discussed cause for that is discrimination against women in the labor market. The aim of the study was to examine evaluation differences between personnel specialists and comparison group, depending on their own and candidate‘s gender. Study was based on quasi-experimental strategy which included a hiring simulation. Participants had to evaluate potential candidates, a man and a woman, seeking for a job in management position. Data was collected from 128 people (age range - 19 to 56 years): 48 personnel specialists (M=29,38; SD=7,48), 49 women, who represented other specialties (M=26,29; SD=7,36) and 31 men, who represented other specialties (M=25,39; SD=5,05). Both personnel specialists and comparison group evaluated man and woman-candidate as similar. There were no significant differences between the two candidates on their hireability, reliability, competence, potential salary and promotability. However, results also indicate that personnel specialists and women, representing other specialties, suggested that man was more capable to work in teams than woman. The study gives an insight about the possibility of gender stereotype change.
Keywords: gender stereotypes; gender discrimination; discrimination against women in the labor market